Severe left heart obstruction with retrograde arch flow influences fetal cerebral and placental blood flow. (2nd September 2013) - Yamamoto, Y.; Khoo, N. S.; Brooks, P. A.; Savard, W.; Hirose, A.; Hornberger, L. K.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2013:42:255–256